Newness and novelty: Relating top management team composition to new venture performance - Amason, Allen C.; Shrader, Rodney C.; Tompson, George H. (Journal of Business Venturing, 2006)
We distinguish novelty from newness and argue that the tasks of new venture top management teams vary with new venture novelty. We argue that as novelty increases, the information processing requirements on the TMT change as well. Because a team's demographic characteristics influence its information processing abilities, venture performance should reflect, at least partially, the fit between the characteristics of the TMT and the level of venture novelty. Evidence from a large sample of ventures supports this view.